從實習學生觀點探討國小數學教學之實習現況與支持策略 - 趙曉美(Chao, Hsiao-Mei); 鍾 靜(Chung, Jing) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2011)
The importance of mathematics teaching expertise of teachers in primary school has been emphasized recently. For ensuring primary school mathematics teachers have enough expertise in mathematics teaching, the research suggests incorporating “mathematics teaching knowledge” into the teacher qualification test. Mentors play a key role for student teachers during the internship. The mentoring strategies adopted directly impact